(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In recent times, we are witnessing the technological revolution which provides access to tremendous changes in all the fields including the industrial sectors. The notable benefit of the modern technology is quick accomplishment of complex tasks within a short span of time, which has motivated the manufacturers to imbibe novelty techniques in the production process to enhance the quality of the product so as to retain its market position amidst the competitors. As globalization has gained more concern, the manufacturers employ internet advertising strategy to elevate the product to international level and to propagate the attributes of the products to the customers residing worldwide. In this paper an EPQ inventory model is developed in which the associated costs of technology, acquisition of local and international customers via internet advertising costs are included, a numerical example is also presented to validate the model.